'Histories of knowledges' for research education. Issue 1 (2nd January 2023) - Qi, Jing; Manathunga, Catherine; Singh, Michael; Bunda, Tracey
ABSTRACT: The world faces complex and entangled environmental, health and social problems that can only be effectively grappled with if the research sector harnesses the knowledges and understandings of diverse cultures. Research education is a key site where more democratic and equitable processes of knowledge creation can take place. Drawing on de Sousa Santos' argument for epistemic justice, this article discusses research education as embedded in global knowledge relations, through introducing the concept histories of knowledges . This concept interrogates the multiple sets of epistemic relations regarding the history of knowledge, the history of science, knowledge movements, and knowledge hierarchies and conditions. Data were collected through surveys, interviews and workshop observations with research candidates and supervisors from Australia, Africa, Asia and Latin America. Findings show that participants demonstrated boundary-crossing awareness of potential knowledge inclusion and creation in non-linear, multilingual and transcultural ways and from perspectives of the Global South. Extending de Sousa Santos' concept of ecologies of knowledges, we apply the conceptual dynamics of histories of knowledges to propose a micro-, meso- and macro-historical approach to research education that centres around reconceptualisation of epistemic relations and repositioning of research candidates and supervisors.